Strategic Management Accounting: Historical Business Performance, Owner-Management Characteristics, Innovation Culture - Antonius Singgih Setiawan; Jamaludin Iskak (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2023)
The use of strategic management accounting is important in modern business management. For this reason, this study aims to examine whether historical business performance, owner-management characteristics, and innovation culture are the key factors influencing MSME owner-management in Palembang City in the use of strategic management accounting techniques in their companies. Using a sample of 114 (76 per cent) respondents from MSME entrepreneurs in the city of Palembang, the research hypothesis was tested using structural equation modeling (SEM) and partial least squares (PLS) analysis with Warp PLS software version 5.0. The results of the study found that historical business performance, owner-management characteristics, and innovation culture had a positive effect on the level of use of strategic management accounting techniques in MSME management in Palembang City.